Gene Expression Analysis of Immunomagnetically Enriched Circulating Tumor Cell Fraction in Castration-Resistant Prostate Cancer - Škereňová, Markéta; Mikulová, Veronika; Čapoun, Otakar; Švec, David; Kološtová, Katarína; Soukup, Viktor; Honová, Hana; Hanuš, Tomáš; Zima, Tomáš (Molecular diagnosis & therapy, 2018)
BACKGROUND: Molecular characterization of tumors could be a key to therapeutic decision-making with regards to targeted therapies in castration-resistant prostate cancer (CRPC). A convenient solution may be non-invasive liquid biopsy testing of circulating tumor cells (CTCs). For this reason, CTC-enriched samples obtained by immunomagnetic separation (AdnaTest®) were studied as a source material for high-throughput gene expression analysis using BioMark™. PATIENTS AND METHODS: CTC-enriched samples from 41 CRPC patients previously determined to be CTC positive using the AdnaTest® were retrospectively re-analysed for androgen receptor (AR) messenger RNA (mRNA), using the updated AdnaTest®. Blood samples were drawn two times from each patient: at the time of CRPC diagnosis and after the third docetaxel cycle. A gene expression panel of 27 genes related to CRPC therapeutic decision-making, including AR full length (ARFL) and splice variant 7 (ARV7), was retrospectively analyzed on a BioMark™ platform in 29 of 41 patients. RESULTS: The AdnaTest® detected AR mRNA in three-quarters of CTC-positive samples taken at the time of CRPC diagnosis and after the third docetaxel cycle. AR detection was associated with a shorter disease-specific survival (45.0 vs. 20.4 months) at the time of CRPC diagnosis. ARFL expression at the time of CRPC diagnosis, measured on the BioMark™ platform, was associated with a lower decrease of serum level of prostate-specific antigen (sPSA) (p = 0.029), i.e., worse therapy response. ARV7 was found in 38% of the ARFL--positive samples at both analyzed timepoints. CONCLUSION: Detection of AR expression by AdnaTest® in CTC-enriched samples may help predict patients' survival. These AdnaTest® CTC-enriched samples can be used in a high-throughput quantitative polymerase chain reaction (qPCR) analysis of gene expression, provided that the specificity of the assay for each individual gene is properly validated. The BioMark™ platform can be used for the simultaneous detection of ARFL and ARV7 and other genes in CTC-enriched samples from CRPC patients.
Keywords: Prostatic Neoplasms, Castration-Resistant; Humans; lidé středního věku; Biomarkers, Tumor; následné studie; rychlé screeningové testy; Aged; imunomagnetická separace; Neoplastic Cells, Circulating; senioři; lidé; nádorové biomarkery; nádory prostaty rezistentní na kastraci; Male; Middle Aged; stanovení celkové genové exprese; transkriptom; nádorové cirkulující buňky; Aged, 80 and over; Real-Time Polymerase Chain Reaction; Transcriptome; senioři nad 80 let; genetické testování; Gene Expression Profiling; Genetic Testing; mužské pohlaví; High-Throughput Screening Assays; kvantitativní polymerázová řetězová reakce; Follow-Up Studies; Immunomagnetic Separation